2020
DOI: 10.1177/0093854820922891
|View full text |Cite
|
Sign up to set email alerts
|

Recidivism Among Justice-Involved Youth: Findings From JJ-TRIALS

Abstract: Recidivism, and the factors related to it, remains a highly significant concern among juvenile justice researchers, practitioners, and policy makers. Recent studies highlight the need to examine multiple measures of recidivism as well as conduct multilevel analyses of this phenomenon. Using data collected in a National Institute on Drug Abuse (NIDA)-funded Juvenile Justice-Translational Research on Interventions for Adolescents in the Legal System (JJ-TRIALS) cooperative agreement, we examined individual- and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 43 publications
(59 reference statements)
0
10
0
Order By: Relevance
“…Previous research found large site differences in recidivism rates during the baseline period (Robertson et al, 2020 ). The overall recidivism rate by site at baseline ranged from 6.4% to 68.8%.…”
Section: Methodsmentioning
confidence: 90%
See 4 more Smart Citations
“…Previous research found large site differences in recidivism rates during the baseline period (Robertson et al, 2020 ). The overall recidivism rate by site at baseline ranged from 6.4% to 68.8%.…”
Section: Methodsmentioning
confidence: 90%
“…Variations in JJ site data documentation and multiple new arrests/referrals to JJ within weeks of the initial intake for some youth called for standardizing how these conditions were interpreted in the study datasets. Cases where multiple new JJ referrals occurred within 30 days of the initial intake were collapsed so that a recidivism event was counted only if a second JJ referral occurred 30 or more days after JJ intake (Robertson et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations